Association between vasomotor symptoms and sarcopenia assessed by L3 skeletal muscle index among Korean menopausal women. Issue 1 (January 2022) - Ryu, Ki-Jin; Kim, Hyun Kyun; Lee, Yeon Ju; Park, Hyuntae; Kim, Tak
Abstract: Objective: To evaluate the association between vasomotor symptoms (VMS), skeletal muscle index (SMI), and sarcopenia in menopausal women. Methods: This cross-sectional study included 295 Korean menopausal women 40 to 65 years old who underwent abdominal computed tomography during routine health checkups between January 2014 and May 2016. The cross-sectional areas of adipose and skeletal muscles were measured at the L3 level using computed tomography. The SMI is defined as the sum of the skeletal muscle area (cm 2 )/height 2 (m 2 ). Sarcopenia was identified by an SMI of <34.9 cm 2 /m 2 . VMS were assessed using the Menopause Rating Scale. Results: The mean age of the participants was 54.93 ± 6.20 years. VMS were reported in 160 women (54.2%). Sarcopenia was more prevalent in women without VMS (18.5%) than in those with (6.9%). Multivariate logistic regression showed that the prevalence of sarcopenia was inversely associated with the prevalence of VMS (odds ratio, 0.32; 95% CI, 0.15-0.67). Moreover, the paraspinal muscle index was positively associated with the prevalence of VMS (odds ratio, 1.06; 95% CI, 1.01-1.11) after adjusting for age, body mass index, waist circumference, adipose tissue area, history of hormone therapy, systolic and diastolic blood pressures, total cholesterol, insulin resistance, alcohol intake, and exercise. Conclusions: VMS are less common in women with sarcopenia than in those without and are positively associated with paraspinal muscle mass in Korean menopausal women. Further longitudinal studies are required to investigate the causal relationships and underlying mechanisms. Abstract : Supplemental Digital Content is available in the text